The Social Sciences in Two Analytical Perspectives on Social Movements in Brazil - Goulart, Débora Cristina (Pontifícia Universidade Católica de São Paulo, 2009)
This work presents a debate between two analytical perspectives from the social sciences on social movements in contemporary Brazil. One view takes as its point of departure the idea that the normalization and legitimation of public-state spaces is a conquest of the movements and proposes the permanent enlargement of social reforms through a new political culture that works through state spaces and the cultural relations of the movements. Another current takes as its point of departure an analysis of the dynamics of social conflict and the class struggle and takes issue with the idea that participation in the government agenda reflects a definitive conquest for social movements. Researchers from these two currents construct analyses using different theoretical and methodological prisms and we attempt here to shed light on the debate between them.